Mesenchymal stromal cells and kidney transplantation: pretransplant infusion protects from graft dysfunction while fostering immunoregulation. (6th June 2013) - Perico, Norberto; Casiraghi, Federica; Gotti, Eliana; Introna, Martino; Todeschini, Marta; Cavinato, Regiane Aparecida; Capelli, Chiara; Rambaldi, Alessandro; Cassis, Paola; Rizzo, Paola; Cortinovis, Monica; Noris, Marina; et al.
Summary Bone marrow‐derived mesenchymal stromal cells (MSC) have emerged as useful cell population for immunomodulation therapy in transplantation. Moving this concept towards clinical application, however, should be critically assessed by a tailor‐made step‐wise approach. Here, we report results of the second step of the multistep MSC‐based clinical protocol in kidney transplantation. We examined in two living‐related kidney transplant recipients whether: (i) pre‐transplant (DAY‐1) infusion of autologous MSC protected from the development of acute graft dysfunction previously reported in patients given MSC post‐transplant, (ii) avoiding basiliximab in the induction regimen improved the MSC‐induced Treg expansion previously reported with therapy including this anti‐CD25‐antibody. In patient 3, MSC treatment was uneventful and graft function remained normal during 1 year follow‐up. In patient 4, acute cellular rejection occurred 2 weeks post‐transplant. Both patients had excellent graft function at the last observation. Circulating memory CD8+ T cells and donor‐specific CD8+ T‐cell cytolytic response were reduced in MSC‐treated patients, not in transplant controls not given MSC. CD4+FoxP3+Treg expansion was comparable in MSC‐treated patients with or without basiliximab induction. Thus, pre‐transplant MSC no longer negatively affect kidney graft at least to the point of impairing graft function, and maintained MSC‐immunomodulatory properties. Induction therapy without basiliximab does not offer any advantage on CD4+FoxP3+Treg expansion (ClinicalTrials.gov number: NCT 00752479).